2018
DOI: 10.3389/fphys.2018.01116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Modeling Assumptions on Stability Predictions in Reverse Total Shoulder Arthroplasty

Abstract: Reverse total shoulder arthroplasty (rTSA) is commonly used in the shoulder replacement surgeries for the relief of pain and to restore function, in patients with grossly deficient rotator cuff. Primary instability due to glenoid loosening is one of the critical complications of rTSA; the implants are designed and implanted such that the motion between the glenoid baseplate and underlying bone is minimized to facilitate adequate primary fixation. Finite element analysis (FEA) is commonly used to simulate the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…To our knowledge, this is the first work to report a full in silico modeling of ASTM F2028-14 for a custom-made prosthesis. Although previous studies [13,14,22] reported FE analysis for a similar experimental set-up, the effect of different loading directions, which in case of a custom implant cannot be neglected due to the asymmetry of the design shape, was never systematically investigated. This approach resulted in a total of eight measurements that were used to support the FE predictions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, this is the first work to report a full in silico modeling of ASTM F2028-14 for a custom-made prosthesis. Although previous studies [13,14,22] reported FE analysis for a similar experimental set-up, the effect of different loading directions, which in case of a custom implant cannot be neglected due to the asymmetry of the design shape, was never systematically investigated. This approach resulted in a total of eight measurements that were used to support the FE predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Major assumptions were made during the creation of the in-silico model, looking for a trade-off between accuracy and computational cost. The bone substitutes were modeled with homogeneous isotropic material properties, a simplification commonly accepted and implemented in the literature [13,14,16,22], although not fully representative of the behavior of the bone substitute. The porous structure of the implant was not explicitly modelled to reduce the complexity of the model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations